Strengthening students' digital literacy for 21st-century learning in Islamic boarding schools - Fikri Dwi Oktaviani; Linda Setiawati (Universitas Pendidikan Indonesia, 2025)
Digital literacy skills are a crucial need in 21st-century education, including in the context of religious-based education such as Islamic boarding schools. Students play a strategic role as the younger generation. Therefore, mastering information technology is essential. However, many students do not have adequate digital access, understanding, and skills. This program was implemented to improve the digital literacy of students at Nurul Mukhlasin Islamic Boarding School. This aims to equip students with relevant digital skills to support 21st-century learning competencies. The methods used were interactive lectures and participatory discussions, adapted to the characteristics of the participants. Evaluation using observation, pretest, and posttest measurements. The results showed a significant increase in three main aspects: understanding the concept of digital literacy, the ability to evaluate information critically, and increasing creativity in producing educational content using digital applications, such as Canva. Digital literacy is a strategic step to supporting 21st-century learning competencies, critical thinking, communication, collaboration, and creativity. Integration of digital literacy into the Islamic boarding school curriculum can form an adaptive and responsible generation. It is recommended to develop a learning ecosystem that supports the sustainability of technology, strengthening the capacity of educators and providing adequate digital infrastructure. Abstrak Keterampilan literasi digital merupakan kebutuhan krusial dalam pendidikan abad ke-21, termasuk dalam konteks pendidikan berbasis agama seperti pesantren. Santri memiliki peran strategis sebagai generasi muda, sehingga penguasaan teknologi informasi menjadi krusial. Meskipun demikian, masih banyak santri yang belum memiliki akses, pemahaman, dan keterampilan digital yang memadai. Program ini dilaksanakan di Pondok Pesantren Nurul Mukhlasin. Kegiatan ini bertujuan membekali santri dengan keterampilan digital yang relevan untuk mendukung kompetensi pembelajaran abad-21. Metode pelaksanaan mencakup ceramah interaktif dan diskusi partisipatif yang disesuaikan dengan karakteristik peserta. Evaluasi dilakukan melalui observasi serta pengukuran pretest-posttest. Hasil kegiatan menunjukkan adanya peningkatan signifikan dalam tiga aspek utama, yakni pemahaman konseptual literasi digital, kemampuan mengevaluasi informasi secara kritis, termasuk mengidentifikasi hoaks dan ujaran kebencian, serta peningkatan kreativitas dalam menghasilkan konten edukatif menggunakan aplikasi digital seperti Canva. Penguatan literasi digital menjadi langkah strategis untuk mendukung kompetensi pembelajaran abad ke-21, seperti berpikir kritis, komunikasi, kolaborasi, dan kreativitas. Oleh karena itu, integrasi literasi digital ke dalam kurikulum pesantren dapat membentuk generasi yang adaptif dan bertanggung jawab. Disarankan agar pesantren mengembangkan ekosistem pembelajaran yang mendukung pemanfaatan teknologi secara berkelanjutan, baik melalui penguatan kapasitas pendidik maupun penyediaan infrastruktur digital yang memadai. Kata Kunci: literasi digital; pembelajaran abad ke-21; pondok pesantren; santri